2013
DOI: 10.1155/2013/362961
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Haemorrhagic Transformation after Thrombolysis for Stroke: A Strategy Utilising Minocycline

Abstract: Haemorrhagic transformation (HT) of recently ischaemic brain is a feared complication of thrombolytic therapy that may be caused or compounded by ischaemia-induced activation of matrix metalloproteinases (MMPs). The tetracycline antibiotic minocycline inhibits matrix MMPs and reduces macroscopic HT in rodents with stroke treated with tissue plasminogen activator (tPA). The West Australian Intravenous Minocycline and TPA Stroke Study (WAIMATSS) aims to determine the safety and efficacy of adding minocycline to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 16 publications
1
24
0
1
Order By: Relevance
“…21 Efficacy and safety of adding minocycline to rtPA in patients is currently evaluated in Australian prospective multicenter study. 22 The fact that we observe an activation of MMP-9 in childhood stroke supports the idea that children might also profit from this add-on therapy.…”
Section: Discussionsupporting
confidence: 75%
“…21 Efficacy and safety of adding minocycline to rtPA in patients is currently evaluated in Australian prospective multicenter study. 22 The fact that we observe an activation of MMP-9 in childhood stroke supports the idea that children might also profit from this add-on therapy.…”
Section: Discussionsupporting
confidence: 75%
“…With the present knowledge about the efficacy of minocycline in reducing the effects of ischemic strokes the authors of the West Australian study known as the Intravenous Minocycline and TPA Stroke Study (WAIMATSS) [68] concluded that: "Minocycline has practical advantages, including its well-established track record of safety (when used as an antibiotic), bioavailability (including orally), and the fact that it can be safely used in patients with hemorrhagic stroke. This makes it a candidate for use in the prehospital setting, without the need for imaging prior to administration.…”
Section: Resultsmentioning
confidence: 99%
“…A study of the effect of administration of minocycline to patients with ischemic stroke is in progress [68]. The purpose of the study is to find out if the risk of ischemic strokes to convert into hemorrhagic strokes is reduced from administration of minocycline.…”
Section: Future Prospects: Replicating the Ninds Studymentioning
confidence: 99%
“…[ 46 ] Various other clinical trials with varying populations have been initiated and pending results. [ 47 ]…”
Section: Drug-based Therapeutics For Ischemic Stroke Treatmentmentioning
confidence: 99%